Synthesis and corrosion inhibition evaluation of novel aminic nitrogen-bearing 1,2,4-triazole Schiff base compounds - Arafa, Wael Abdel Gayed Ahmed; El-Sayed, Nady Hashem (European Journal of Chemistry, 2014)
Simple, effective, and high yield synthetic procedure for the synthesis of Schiff bases 5a-c is described. The scope of this reaction was investigated and noted that the presence of nickel(II) nitrate hexahydrate gave the corresponding Schiff bases in excellent yields. The inhibition effects of N-((1-phenyl-3-(thiophen-2-yl)-1H-pyrazol-5-yl)methylene)-4H-1,2,4-triazol-3-amine (PTP), 5c, have been investigated against the corrosion of copper in 0.5 M HCl solution. The investigations were accomplished using potentiodynamic polarization and electrochemical impedance measurements. Potentiodynamic polarization measurements indicated that the examined compound is mixed-type inhibitor. The results of electrochemical impedance indicated that the values of the charge transfer resistance and the inhibition efficiency tend to be increased by increasing the inhibitor concentration.